Pewarnaan Titik pada Keluarga Graf Sentripetal - Istamala Idha Retnoningsih; Dafik Dafik; Saddam Hussen (CGANT JOURNAL OF MATHEMATICS AND APPLICATIONS, 2022)
The graph $G$ is defined as a pair of sets $(V,E)$ denoted by $G=(V,E)$, where $V$ is a non-empty vertex set and $E$ is an edge set may be empty connecting a pair of vertex. Two vertices $u$ and $v$ in the graph $G$ are said to be adjacent if $u$ and $v$ are endpoints of edge $e=uv$. The degree of a vertex $v$ on the graph $G$ is the number of vertices adjacent to the vertex $v$. In this study, the topic of graphs is vertex coloring will be studied. Coloring of a graph is giving color to the elements in the graph such that each adjacent element must have a different color. Vertex coloring in graph $G$ is assigning color to each vertex on graph $G$ such that the adjecent vertices $u$ and $v$ have different colors. The minimum number of colorings produced to color a vertex in a graph $G$ is called the vertex chromatic number in a graph $G$ denoted by $χ(G)$.